Blogging the Maternal: Self-Representations of the Pregnant and Postpartum Body - Husbands, Lesley (Atlantis)

(untitled) (Mount Saint Vincent University, 2008)
This paper analyzes how dominant media images of the pregnant and postpartum body contribute to women's self-perceptions and it evaluates how the content of the blog reflects, reinforces (inadvertently) and challenges Western cultural understandings of pregnancy and mothering.